FEASIBILITY OF REUSING PFF2 RESPIRATORS DURING THE COVID-19 PANDEMIC IN BRAZIL: QUASI-EXPERIMENTAL STUDY - Schneider, Daniela Silva dos Santos; Magalhães, Ana Maria Müller de; Oliveira, João Lucas Campos de; Tanaka, Ana Karina Silva da Rocha (Cogitare Enfermagem, 2024)
Objective: Evaluate the feasibility of decontaminating PFF2 respirators in pandemic situations. Method: Quasi-experiment in a public hospital in South Brazil between April and June 2021. The sample consisted of PFF2 respirators used for six and 42 hours in the intensive care unit, divided into groups (usage time and types of intervention) and a control group. They were evaluated for resistance, integrity, and flammability. Descriptive and inferential statistics were used to compare multiple groups to verify whether the respirator remained safe after decontamination, among the different treatments and the mask usage time. Results: There was a significant difference in filter efficiency (p=0.002) and resistance (p<=0.001) between PFF2. Decontaminations did not influence integrity when their interaction with usage time was evaluated. Conclusion: Decontamination, separately or together, was a viable alternative.